2011
DOI: 10.1021/ie101129k
|View full text |Cite
|
Sign up to set email alerts
|

Improved Tank in Series Model for the Planar Solid Oxide Fuel Cell

Abstract: Models of different complexity are required in the iterative process of designing a solid oxide fuel cell (SOFC). Models having less complexity and computational dexterity are the ideal ones at the early stages. This work presents the development of an improved tank in series reactor model of the SOFC operating in cocurrent, countercurrent, and cross-current flow directions. The model, which accounts for the charge balances in the electrodes and electrolyte in addition to the component balances and the energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Even though the model is 0D at the compartment scale, it becomes a 1D, 2D and 3D model at the channel, cell and stack scales, respectively, as shown in Figure 1. The governing conservation and constitutive equations are taken from Hosseini et al (2010) and Danilov et al (2011b) and adapted for a single compartment. The model parameters and operating conditions are the same as those used in Hosseini et al (2010).…”
Section: Model and Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the model is 0D at the compartment scale, it becomes a 1D, 2D and 3D model at the channel, cell and stack scales, respectively, as shown in Figure 1. The governing conservation and constitutive equations are taken from Hosseini et al (2010) and Danilov et al (2011b) and adapted for a single compartment. The model parameters and operating conditions are the same as those used in Hosseini et al (2010).…”
Section: Model and Parametersmentioning
confidence: 99%
“…The governing conservation and constitutive equations are taken from Hosseini et al (2010) and Danilov et al (2011b) and adapted for a single compartment. The model parameters and operating conditions are the same as those used in Hosseini et al (2010). The model equations and the simulation parameters are summarised in Tables A1 and A2.…”
Section: Model and Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…At steady state, the rate of mass transfer in Eqs. (10) and (11) is balanced by the rate of electrochemical reaction.…”
Section: Model Equationsmentioning
confidence: 99%
“…In earlier studies we reported a dynamic TSR model for a PEMFC [9] and planar SOFC [10]. These improved TSR models include species and energy balances in gas channels and liquid electrolyte phase together with charge balance equations defined at the electrode-electrolyte interfaces.…”
Section: Introductionmentioning
confidence: 99%